Method for removing copper-humic acid of different molecular weight by adsorption and synergistic oxidation of manganese oxide modified biomass charcoal

CN121377193BActive Publication Date: 2026-10-27BEIHANG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511356668.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-09-22
Publication Date
2026-10-27
Estimated Expiration
2045-09-22

AI Technical Summary

Technical Problem

目前已有研究分析了利用吸附和高级氧化法去除水体中HA,但HA是一种复杂且无确定分子量和结构的物质,不同分子量的腐殖酸性质不同,与金属络合能力不同

Benefits of technology

[0024]本发明的技术效果如下:本发明锰氧化物改性生物质炭吸附协同氧化去除不同分子量腐殖酸铜方法(其中包含机制分析方法),包含负载型锰氧化物改性生物质炭合成以及不同分子量腐殖酸铜络合物去除性能的研究,可去除不同分子量的腐殖酸铜络合物,小于1KDa的铜络合物可实现95%的铜去除,大于100KDa的铜络合物可实现70%的铜去除,且五种组分的TOC去除率均保持在90%以上,小于1KDa的铜络合物在水体中以絮状物存在,其去除主要以吸附作用为主;大于1KDa的铜络合物去除是利用锰氧化物改性生物质炭作为催化剂和吸附剂,利用羟基自由基将长链烷烃类、苯环类和杂环类腐殖酸铜络合物降解成可被吸附的小分子有机物和Cu的络合物。本发明的锰氧化物改性生物炭能够高效去除不同分子量的腐殖酸铜络合物,具有低成本、高效、无二次污染等优点。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121377193B_ABST
    Figure CN121377193B_ABST
Patent Text Reader

Abstract

The method for removing copper humic acid complexes of different molecular weights by adsorption and synergistic oxidation of manganese oxide modified biomass charcoal comprises synthesis of manganese oxide modified biomass charcoal and research on removal performance of copper humic acid complexes of different molecular weights. Copper humic acid complexes of different molecular weights can be removed. Copper complexes less than 1 KDa can achieve 95% copper removal, and copper complexes greater than 100 KDa can achieve 70% copper removal. The TOC removal rates of the five components are all kept above 90%. The removal of copper complexes less than 1 KDa is mainly based on the adsorption of manganese oxide modified biomass charcoal. The removal of copper complexes greater than 1 KDa is based on the use of manganese oxide modified biomass charcoal as a catalyst and an adsorbent, the use of hydroxyl radicals generated by catalysis to degrade long-chain alkane, benzene ring and heterocyclic humic acid copper complexes into small-molecule organic matter and Cu complexes that can be adsorbed, and the removal of copper humic acid complexes of different molecular weights based on the adsorption capacity of modified biomass charcoal.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of complexed heavy metal treatment, specifically relating to a method for removing copper humates of different molecular weights by adsorption and synergistic oxidation using manganese oxide-modified biochar. Background Technology

[0002] Water pollution is a key environmental concern. Besides metal and organic pollution, there is also the issue of complexed metal pollutants. Complexed metals in water bodies are mainly organometallic complexes generated by human activities and complexes formed by the complexation of natural organic matter with metal ions. The latter are widely distributed in various water bodies, with significant differences in concentration. Natural organic matter is mainly composed of humic acid (HA), fulvic acid, proteins, and other substances. HA is a class of natural organic macromolecules produced from the decomposition and transformation of plant and animal remains by microorganisms. It has a strong ion exchange capacity and readily interacts with metals to form stable metal complexes, further affecting the toxicity, transfer, and removal of metals. Therefore, the removal of metal complexes formed by natural organic matter has become an urgent task in metal removal.

[0003] Currently, methods for removing metals and organic matter include oxidation, adsorption, electro / photocatalysis, and membrane separation. Adsorption has played a crucial role in water pollution control due to its advantages such as readily available and easily prepared adsorbents, high efficiency, and cost-effectiveness. Biochar materials possess a multidimensional porous structure, enabling them to efficiently adsorb metals from water. They also offer advantages such as rich structural diversity, good compatibility, and low cost. Furthermore, biochar modification can expand its adsorption capacity. For example, iron and manganese oxides are widely present in the Earth's crust and are chemically stable substances. Under certain conditions, these metal oxides can facilitate electron transport, which can aid in the transformation and degradation of organic matter. Functionalized biochar not only leverages its inherent excellent adsorption capacity but also exhibits oxidation and catalytic effects on metals. Current research has analyzed the removal of humic acid (HA) from water using adsorption and advanced oxidation methods. However, HA is a complex substance without a defined molecular weight and structure; humic acids of different molecular weights have different properties and varying metal complexation abilities. Therefore, the removal pathways and removal performance are quite different. It is meaningful to refine the complex humic acid according to its molecular weight, study the complexation properties of HA with metals of different molecular weights, and explore the removal mechanism in detail.

[0004] This invention classifies HA according to molecular weight and complexes it with copper to obtain humic acid copper complex (HA-Cu). It analyzes the performance of manganese oxide modified biochar in removing humic acid copper complexes of different molecular weights, investigates the influence of environmental factors on the removal capacity of humic acid copper complex, and deepens the removal mechanism of manganese oxide modified biochar in humic acid copper complex. This lays the analytical and mechanistic foundation for future research on the removal of more complexed metals. Summary of the Invention

[0005] This invention addresses the shortcomings of existing technologies by providing a method for removing copper humate of different molecular weights through adsorption and synergistic oxidation using manganese oxide-modified biochar. Copper humate, specifically humic acid-copper complex (HA-Cu), is a copper organic complex pollutant. By classifying HA-Cu according to molecular weight, the adsorption of HA-Cu with a molecular weight below 1 kDa is utilized, while the synergistic effect of adsorption and catalytic oxidation of HA-Cu with a molecular weight above 1 kDa is employed. The catalytic oxidation mechanism utilizes hydroxyl radicals to degrade long-chain alkanes, benzene rings, and heterocyclic copper humate complexes into adsorbable small-molecule organic compounds and Cu complexes. Research has verified that this method achieves a copper removal rate of ≥95% for low molecular weight HA-Cu and ≥70% for high molecular weight HA-Cu, with the TOC removal rate of all five components remaining above 90%.

[0006] The technical solution of the present invention is as follows:

[0007] A method for removing copper humates of different molecular weights by adsorption and synergistic oxidation using manganese oxide-modified biochar is characterized by the following steps: HA-Cu is divided according to molecular weight; HA-Cu with a molecular weight below 1 kDa is removed by adsorption using manganese oxide-modified biochar; and HA-Cu with a molecular weight above 1 kDa is removed by a combination of adsorption and catalytic oxidation using manganese oxide-modified biochar. The catalytic oxidation utilizes hydroxyl radicals to degrade long-chain alkanes, benzene rings, and / or heterocyclic copper humates in high molecular weight humic acid HA into adsorbable small-molecule organic compounds and / or small-molecule Cu complexes.

[0008] The manganese oxide-modified biochar is prepared using the following steps:

[0009] Step 1: Mix biochar BC and anhydrous ethanol to form a first mixture;

[0010] Step 2: After continuously stirring the first mixture for 4 hours, slowly add KMnO4 solution to form the second mixture;

[0011] Step 3: After stirring the second mixture for 2 hours, filter it with 0.45 μm qualitative filter paper to obtain the retentate. Wash the retentate with ultrapure water to obtain the initial sample.

[0012] Step 4: Place the initial sample in a constant temperature drying oven at 90℃ for 12 hours to obtain the intermediate sample;

[0013] Step 5: Place the intermediate sample in a tube furnace and heat it to 500℃ at a rate of 5℃ / min under nitrogen atmosphere protection. Hold the temperature for 1 hour. After the program is completed, automatically cool it to room temperature to obtain the final sample, i.e., manganese oxide modified biochar. Name the final sample BC-MnOx-500, where x is a positive integer.

[0014] In step 1, BC is 60-80 mesh coconut shell biochar particles. 1g of BC and 20mL of anhydrous ethanol are selected. In step 2, 20mL of KMnO4 solution is used. The concentration of KMnO4 solution is 0.1M.

[0015] The following steps were taken to analyze the performance of manganese oxide-modified biochar in removing copper humates of different molecular weights:

[0016] Step A: Prepare copper humate complex solution;

[0017] Step B, performance analysis: BC-MnOx-500 and H2O2 were added to the copper humate complex solution to form a mixture. The mixture was placed in a constant temperature shaker at 150 rpm and set temperature and rotated continuously for 10 hours. Samples were taken every 1 hour. The samples were filtered through a 0.45 μm polyethersulfone (PES) membrane, acidified with 2 wt% HNO3, and the concentrations of Cu and Mn were analyzed by inductively coupled plasma mass spectrometry. The total organic carbon (TOC) content of the un-acidified filtered samples was analyzed using an organic carbon analyzer.

[0018] Step C, Analysis of influencing factors: Under the determined dosage conditions, the effects of pH value, common coexisting ions and different temperatures on the removal performance of HA-Cu complex and the stability of the material were analyzed.

[0019] Step D, Removal Mechanism Analysis: Combining changes in the material surface structure and EEM and CE analyses of the structural changes in the solution during the removal process, the removal mechanism is inferred.

[0020] Step A includes: dissolving 1g of humic acid solid powder in 1L of NaOH solution (0.025M concentration), stirring at room temperature in the dark for 3 hours, filtering using a 0.45μm aqueous filter membrane, and adjusting the pH of the obtained humic acid (HA) stock solution to 7 with 0.1M HNO3. Ultrafiltration fractionation is then used to obtain HA solutions with different molecular weights, labeled UF1 to UF5. UF1 corresponds to a HA molecular weight > 100kDa, 100kDa ≥ UF2 corresponds to a HA molecular weight > 30kDa, 30kDa ≥ UF3 corresponds to a HA molecular weight > 10kDa, 10kDa ≥ UF4 corresponds to a HA molecular weight > 1kDa, and UF5 corresponds to a HA molecular weight < 1kDa. Cu is added to each of the five different molecular weight HA solutions. 2+Five mixed solutions were then placed in a constant temperature shaker at 25°C and equilibrated for 12 hours to achieve complete complexation. The complexed solutions were named UF1-Cu, UF2-Cu, UF3-Cu, UF4-Cu and UF5-Cu, respectively.

[0021] The amounts of BC-MnOx-500 added in step B, expressed in g / L, were 0, 0.5, 1.0, 1.5, and 2.0, respectively, and the amounts of H2O2 added, expressed in mM, were 100, 150, 200, 250, and 300, respectively.

[0022] In step C, the pH conditions are set to 4, 6, 7, 8, and 10, respectively. Common coexisting ions include Ca2+. 2+ Na + CO3 2- and SO4 2- The different temperature conditions were set to 20℃, 25℃ and 30℃ respectively.

[0023] In step D, the analysis and testing involve three-dimensional fluorescence and capillary electrophoresis to analyze the structural changes of HA-Cu with different molecular weights during the removal process, and to test the changes in surface functional groups and structure of the material after the removal process.

[0024] The technical effects of this invention are as follows: This invention provides a method for the adsorption and synergistic oxidation of copper humate complexes of different molecular weights using manganese oxide-modified biochar (including mechanistic analysis methods). It includes the synthesis of supported manganese oxide-modified biochar and research on the removal performance of copper humate complexes of different molecular weights. It can remove copper humate complexes of different molecular weights; 95% removal of copper complexes less than 1 kDa and 70% removal of copper complexes greater than 100 kDa are achieved. Furthermore, the TOC removal rate of all five components remains above 90%. Copper complexes less than 1 kDa exist as flocculents in water, and their removal is mainly through adsorption. The removal of copper complexes greater than 1 kDa utilizes manganese oxide-modified biochar as a catalyst and adsorbent, using hydroxyl radicals to degrade long-chain alkanes, benzene rings, and heterocyclic copper humate complexes into adsorbable small-molecule organic matter and Cu complexes. The manganese oxide-modified biochar of this invention can efficiently remove copper humate complexes of different molecular weights, offering advantages such as low cost, high efficiency, and no secondary pollution.

[0025] The features of this invention are as follows:

[0026] (1) This invention provides a simple method to synthesize manganese oxide modified biochar and efficiently remove copper humate of different molecular weights. The low molecular weight copper complex can achieve a copper removal rate of more than 95%, and the high molecular weight copper humate complex can achieve a copper removal rate of more than 70%.

[0027] (2) This invention provides a performance analysis of manganese oxide modified biochar for removing copper complexes from humic acid. The removal performance of complexed copper is related to the molecular weight of humic acid. Low molecular weight complexed copper is mainly adsorbed, while the removal of high molecular weight copper complexes is a synergistic effect of adsorption and catalytic oxidation. This provides theoretical support for the analysis of the removal of complexes of natural organic matter and metals in water. Attached Figure Description

[0028] Figure 1a These are biochar morphology diagrams used in implementing the manganese oxide modified biochar adsorption and synergistic oxidation method for removing copper humates of different molecular weights according to the present invention. Figure 1a The morphology of biomass char (BC) was observed using field emission scanning electron microscopy (FE-SEM). The surface of BC was very smooth.

[0029] Figure 1b These are morphological images of manganese oxide-modified biochar involved in the implementation of the method for removing copper humates of different molecular weights by adsorption and synergistic oxidation using manganese oxide-modified biochar according to the present invention. Figure 1b The biochar modified with manganese oxide was named BC-MnOx-500. The morphology of BC-MnOx-500 shows that it consists of uniformly dispersed nanoparticles with a relatively uniform particle size (approximately 90 nm). Figure 1b The morphology of the manganese oxide-modified biochar was observed using field emission scanning electron microscopy (FE-SEM).

[0030] Figure 2a These are the Fourier transform infrared spectra of BC and BC-MnOx-500. Figure 2a The Fourier Transform Infrared (FTIR) technique was used to confirm that manganese oxides were loaded on the surface of biochar.

[0031] Figure 2b These are the X-ray diffraction patterns of BC and BC-MnOx-500. Figure 2b The XRD (X-ray Diffraction) technology is used. Figure 2b The mid-angle 2θ diffraction peaks at 18.0°, 28.9° and 35.1°, 40.5° correspond to Mn3O4 and MnO substances, respectively.

[0032] Figure 3a This is a graph showing the effect of BC-MnOx-500 dosage on the Cu removal rate in HA-Cu.

[0033] Figure 3bThis is a graph showing the effect of BC-MnOx-500 dosage on the TOC removal rate in HA-Cu. TOC stands for Total Organic Carbon.

[0034] Figure 4a This is a graph showing the effect of H2O2 dosage on the Cu removal rate in HA-Cu.

[0035] Figure 4b This is a graph showing the effect of H2O2 dosage on the TOC removal rate in HA-Cu.

[0036] Figure 5a This is the UV-Vis spectrum of the solution after removal. UV-Vis stands for ultraviolet-visible.

[0037] Figure 5b The method involves using fluorescence spectrophotometry to determine the content of HO· generated in the removal system.

[0038] Figure 6a This is a graph showing the effect of solution pH on the Cu removal rate in HA-Cu.

[0039] Figure 6b This is a graph showing the effect of solution pH on the TOC removal rate in HA-Cu.

[0040] Figure 7a This is a graph showing the effect of coexisting ions on the Cu removal rate in HA-Cu.

[0041] Figure 7b This is a graph showing the effect of coexisting ions on the TOC removal rate in HA-Cu.

[0042] Figure 8a This is a graph showing the effect of temperature on the Cu removal rate in HA-Cu.

[0043] Figure 8b This is a graph showing the effect of temperature on the TOC removal rate in HA-Cu.

[0044] Figure 9 This is the EEM spectrum of the HA-Cu removal process. EEM is a three-dimensional fluorescence spectrum. Figure 9 In the middle sub-figure a0, 'a' represents the UF5-Cu component among the five HA-Cu components. '0' represents the reaction time of 0 hours, '1' represents the reaction time of 1 hour, '2' represents the reaction time of 4 hours, and '3' represents the reaction time of 8 hours. In sub-figure b0, 'b' represents the UF4-Cu component, 'c' in 'c0' represents the UF3-Cu component, 'd' in 'd0' represents the UF2-Cu component, and 'e' in 'e0' represents the UF1-Cu component. 'Ex' represents the excitation wavelength (i.e., the y-axis or vertical axis, nm, scale value 200, 400, 600), and 'Em' represents the emission wavelength (i.e., the x-axis or horizontal axis, nm, scale value 200, 400, 600).

[0045] Figure 10This is the CE spectrum of the HA-Cu removal process. CE stands for capillary electrophoresis, Abs is the absorbance (i.e., y-axis or vertical axis, scale values ​​from 0.000, 0.001 to 0.008), and Time is the time (i.e., x-axis or horizontal axis, min, minutes, scale values ​​from 2, 3 to 10). Figure 10 Sub-plot a includes UF5 curve, UF5-Cu curve, 1h curve, 4h curve, 8h curve, and 10h curve; sub-plot b includes UF4 curve, UF4-Cu curve, 1h curve, 4h curve, 8h curve, and 10h curve; sub-plot c includes UF3 curve, UF3-Cu curve, 1h curve, 4h curve, 8h curve, and 10h curve; sub-plot d includes UF2 curve, UF2-Cu curve, 1h curve, 4h curve, 8h curve, and 10h curve; and sub-plot e includes UF1 curve, UF1-Cu curve, 1h curve, 4h curve, 8h curve, and 10h curve.

[0046] Figure 11 This is a SEM image of BC-MnOx-500 after removal. Figure 11 In the diagram, 'a' represents the material used to remove UF5-Cu, and 'b' represents the material used to remove UF4-Cu. Figure 11 In the diagram, c represents the material used to remove UF3-Cu. Figure 11 In the diagram, d represents the material used to remove UF2-Cu. Figure 11 In the diagram, 'e' represents the material from which UF1-Cu was removed. SEM stands for Scanning Electron Microscopy.

[0047] Figure 12a This is the FTIR after BC-MnOx-500 removal. FTIR stands for Fourier Transform Infrared.

[0048] Figure 12b This is an analysis of Cu element in the XPS of the removed material.

[0049] Figure 12c For nitrogen elemental analysis of the material after removal. XPS, or X-ray photoelectron spectroscopy, is used to analyze the type, chemical state, and changes in molecular structure of elements. Detailed Implementation

[0050] The following is in conjunction with the attached diagram ( Figures 1a-12c The invention will be described in the following sections and examples.

[0051] Figure 1a These are biochar morphology diagrams used in implementing the manganese oxide modified biochar adsorption and synergistic oxidation method for removing copper humates of different molecular weights according to the present invention. Figure 1b These are morphological images of manganese oxide-modified biochar involved in the implementation of the method for removing copper humates of different molecular weights by adsorption and synergistic oxidation using manganese oxide-modified biochar according to the present invention. Figure 2a These are the Fourier transform infrared spectra of BC and BC-MnOx-500. Figure 2b These are the X-ray diffraction patterns of BC and BC-MnOx-500. Figure 3a This is a graph showing the effect of BC-MnOx-500 dosage on the Cu removal rate in HA-Cu. Figure 3b This is a graph showing the effect of BC-MnOx-500 dosage on the TOC removal rate in HA-Cu.

[0052] Figure 4a This is a graph showing the effect of H2O2 dosage on the Cu removal rate in HA-Cu. Figure 4b This is a graph showing the effect of H2O2 dosage on the TOC removal rate in HA-Cu. Figure 5a This is the UV-Vis spectrum of the solution after removal. Figure 5b The method involves using fluorescence spectrophotometry to determine the content of HO· in different systems. Figure 6a This is a graph showing the effect of solution pH on the Cu removal rate in HA-Cu. Figure 6b This is a graph showing the effect of solution pH on the TOC removal rate in HA-Cu. Figure 7a This is a graph showing the effect of coexisting ions on the Cu removal rate in HA-Cu. Figure 7b This is a graph showing the effect of coexisting ions on the TOC removal rate in HA-Cu. Figure 8a This is a graph showing the effect of temperature on the Cu removal rate in HA-Cu. Figure 8b This is a graph showing the effect of temperature on the TOC removal rate in HA-Cu. Figure 9 This is the EEM image of the HA-Cu removal process. Figure 10 This is the CE spectrum of the HA-Cu removal process. Figure 11 This is a SEM image of BC-MnOx-500 after removal. Figure 12a It is the FTIR after BC-MnOx-500 removal. Figure 12b This is an analysis of Cu element in the XPS of the removed material. Figure 12c For nitrogen elemental analysis of the material after removal. (Reference) Figures 1a to 12c As shown, the method for removing copper humates of different molecular weights by adsorption and synergistic oxidation using manganese oxide-modified biochar includes dividing HA-Cu according to molecular weight, removing HA-Cu with a molecular weight below 1 kDa by adsorption using manganese oxide-modified biochar, and removing HA-Cu with a molecular weight above 1 kDa by synergistic adsorption and catalytic oxidation using manganese oxide-modified biochar. The catalytic oxidation utilizes hydroxyl radicals to degrade long-chain alkanes, benzene rings, and / or heterocyclic copper humates in high molecular weight humic acid HA into small molecule organic matter and / or small molecule complexes of Cu that can be adsorbed.

[0053] The manganese oxide modified biochar is prepared by the following steps: Step 1, biochar BC and anhydrous ethanol are mixed to form a first mixture; Step 2, after stirring the first mixture for 4 hours, KMnO4 solution is slowly added to form a second mixture; Step 3, after stirring the second mixture for 2 hours, it is filtered with 0.45μm qualitative filter paper to obtain the retentate, and the retentate is washed with ultrapure water to obtain the initial sample; Step 4, the initial sample is placed in a constant temperature drying oven at 90℃ for 12 hours to obtain an intermediate sample; Step 5, the intermediate sample is placed in a tube furnace and heated to 500℃ at a heating rate of 5℃ / min under nitrogen atmosphere protection and held at that temperature for 1 hour. After the program ends, it is automatically cooled to room temperature to obtain the final sample, i.e., manganese oxide modified biochar, which is named BC-MnOx-500, where x is a positive integer.

[0054] In step 1, BC is 60-80 mesh coconut shell biochar particles. 1g of BC and 20mL of anhydrous ethanol are selected. In step 2, 20mL of KMnO4 solution is used. The concentration of KMnO4 solution is 0.1M.

[0055] The following steps were taken to analyze the removal performance of copper humate of different molecular weights using manganese oxide-modified biochar: Step A, preparation of copper humate complex solution; Step B, removal performance analysis: BC-MnOx-500 and H2O2 were added to the copper humate complex solution to form a mixture. The mixture was placed in a constant temperature shaker at 150 rpm for 10 hours, and samples were taken every hour. The samples were filtered through a 0.45 μm polyethersulfone (PES) membrane, acidified with 2 wt% HNO3, and the Cu and Mn concentrations were analyzed by inductively coupled plasma mass spectrometry. The total organic carbon (TOC) content of the un-acidified filtered samples was analyzed using an organic carbon analyzer; Step C, analysis of influencing factors: under determined dosage conditions, the effects of pH, common coexisting ions, and different temperatures on the removal performance and material stability of HA-Cu complexes were analyzed. Step D, the mechanism for removing copper humate complexes of different molecular weights was determined by analyzing the changes in material morphology and structure combined with changes in solution properties during the removal process to identify the adsorption and catalytic oxidation mechanisms.

[0056] Step A includes: dissolving 1g of humic acid solid powder in 1L of NaOH solution (0.025M concentration), stirring at room temperature in the dark for 3 hours, filtering using a 0.45μm aqueous filter membrane, and adjusting the pH of the obtained humic acid (HA) stock solution to 7 with 0.1M HNO3. Ultrafiltration fractionation is then used to obtain HA solutions with different molecular weights, labeled UF1 to UF5. UF1 corresponds to a HA molecular weight > 100kDa, 100kDa ≥ UF2 corresponds to a HA molecular weight > 30kDa, 30kDa ≥ UF3 corresponds to a HA molecular weight > 10kDa, 10kDa ≥ UF4 corresponds to a HA molecular weight > 1kDa, and UF5 corresponds to a HA molecular weight < 1kDa. Cu is added to each of the five different molecular weight HA solutions. 2+ Five mixed solutions were then formed and placed in a constant-temperature shaker at 25°C for 12 hours to achieve complete complexation. The complexed solutions were named UF1-Cu, UF2-Cu, UF3-Cu, UF4-Cu, and UF5-Cu, respectively. In step B, the amounts of BC-MnOx-500 added (g / L) were 0, 0.5, 1.0, 1.5, and 2.0, respectively, and the amounts of H2O2 added (mM) were 100, 150, 200, 250, and 300, respectively. In step C, the pH conditions were set to 4, 6, 7, 8, and 10, respectively. Common coexisting ions included Ca2+. 2 + Na + CO3 2- and SO4 2- The different temperature conditions were set to 20℃, 25℃ and 30℃ respectively.

[0057] This invention discloses a method for the adsorption and synergistic oxidation of copper humate complexes of different molecular weights using manganese oxide-modified biochar. The method includes the synthesis of supported manganese oxide-modified biochar and the study of the removal performance of copper humate complexes of different molecular weights. The manganese oxide-modified biochar prepared by this method can remove copper humate complexes of different molecular weights. Copper complexes less than 1 kDa can achieve 95% copper removal (kDa, kilodalton), and copper complexes greater than 100 kDa can achieve 70% copper removal. Furthermore, the TOC removal rate (total organic carbon) of all five components remains above 90%. Modified biochar exhibits good adsorption capacity, catalytic ability, and excellent stability. The removal mechanism of copper humic acid complexes is related to the molecular weight of humic acid. Copper complexes smaller than 1 kDa exist as flocculents in water, and their removal is mainly through adsorption. The removal of copper complexes larger than 1 kDa utilizes manganese oxide-modified biochar as a catalyst and adsorbent, employing hydroxyl radicals to degrade long-chain alkanes, benzene rings, and heterocyclic copper humic acid complexes into adsorbable small-molecule organic compounds and Cu complexes. The manganese oxide-modified biochar adsorbent of this invention can efficiently adsorb complexed metal pollutants, offering advantages such as low cost, high efficiency, and no secondary pollution.

[0058] The present invention presents a performance analysis and mechanism study on the removal of copper humates of different molecular weights using manganese oxide-modified biochar, which mainly includes the following two steps:

[0059] Step 1: Preparation of manganese oxide modified biochar;

[0060] Preparation of manganese oxide modified biochar: 60-80 mesh coconut shell biochar particles were selected. BC (1g) was mixed with 20mL of anhydrous ethanol and stirred continuously for 4h. Then, 20mL of KMnO4 solution (0.1M) was slowly added and stirred continuously for 2h. The mixture was then filtered through 0.45μm qualitative filter paper and washed with ultrapure water. The washed sample was placed in a constant temperature drying oven at 90℃ for 12h. The dried material was placed in a tube furnace and heated to 500℃ at a rate of 5℃ / min under nitrogen atmosphere protection and held at that temperature for 1h. After the program ended, the material was automatically cooled to room temperature. The sample was named BC-MnOx-500.

[0061] Step 2: Performance analysis of manganese oxide modified biochar in removing copper humates of different molecular weights;

[0062] (1) Preparation of copper humic acid complex: 1 g of humic acid solid powder was dissolved in 1 L of 0.025 M NaOH solution and stirred at room temperature in the dark for 3 h. The solution was then filtered using a 0.45 μm aqueous filter membrane. The pH of the obtained HA stock solution was adjusted to 7 using 0.1 M HNO3. The molecular weight cutoff of HA was set to 100, 30, 10 and 1 kDa. Ultrafiltration fractionation was performed using a Millipore ultrafiltration unit equipped with a 76.0 mm diameter modified cellulose acetate membrane. To reduce the influence of concentration polarization, the ultrafiltration process was carried out sequentially from high molecular weight to low molecular weight. During the fractionation process, 0.1 MPa N2 was used as the driving pressure to maintain an outflow rate of 1-2 drops / second. The ultrafiltration retention ratio was 1:5. The five HA solutions obtained by ultrafiltration fractionation had molecular weight ranges of >100, 100-30, 30-10, 10-1, and <1 kDa, and were labeled as UF1, UF2, UF3, UF4, and UF5, respectively. 2+ The concentration was set at 5 mg / L, HA:Cu = 3:1 (TOC:Cu (mg / L)), and the mixed solution was placed in a constant temperature shaker at 25℃ and equilibrated for 12 h to achieve complete complexation. The complexed solutions were named UF1-Cu, UF2-Cu, UF3-Cu, UF4-Cu and UF5-Cu, respectively.

[0063] (2) Removal performance and mechanism analysis: A certain amount of BC-MnOx-500 (0.5, 1.0, 1.5 and 2.0 g / L, and 0 added) and H2O2 (100, 150, 200, 250 and 300 mM) were added to 20 mL of HA-Cu complex solution and placed in a constant temperature shaker at 150 rpm for 10 h. Samples were taken every 1 h. The samples were filtered through a 0.45 μm PES membrane, acidified with 2% HNO3, and the Cu and Mn concentrations were analyzed by inductively coupled plasma mass spectrometry. The TOC content of the un-acidified filtered samples was analyzed by an organic carbon analyzer. The changes in characteristic fluorescent groups of HA-Cu with different molecular weights were analyzed by three-dimensional fluorescence analysis, and the changes in the complex structure of HA-Cu with different molecular weights were analyzed by capillary electrophoresis. The removal mechanism was revealed by combining the morphological and structural changes of the material after removal.

[0064] (3) Analysis of influencing factors: Under the determined dosage conditions, the pH (pH = 4, 6, 7, 8 and 10) and common coexisting ions Ca2+ were analyzed. 2+ Na + CO3 2- and SO4 2- Effects of 10 mM and different temperatures (20, 25 and 30 °C) on the removal performance and material stability of HA-Cu complex.

[0065] Example 1:

[0066] This embodiment provides the preparation of manganese oxide modified biochar, including the following steps:

[0067] (1) Material preparation: 60-80 mesh coconut shell biochar, KMnO4 solution, anhydrous ethanol;

[0068] (2) Preparation of manganese oxide modified biochar: 60-80 mesh coconut shell biochar particles BC (1g) were mixed with 20mL of anhydrous ethanol and stirred continuously for 4h. Then, 20mL of KMnO4 solution (0.1M) was slowly added and stirred continuously for 2h. The mixture was then filtered with 0.45μm qualitative filter paper and washed with ultrapure water. The washed sample was placed in a constant temperature drying oven at 90℃ for 12h. The dried material was placed in a tube furnace and heated to the set temperature of 500℃ at a heating rate of 5℃ / min under N2 atmosphere protection and held at that temperature for 1h. After the program ended, the material was automatically cooled to room temperature. The obtained material was named BC-MnOx-500. Figure 1a The morphology is BC, and it can be seen that the surface of BC is very smooth. Figure 1b The morphology is BC-MnOx-500, indicating that the surface nanoparticles are uniformly dispersed and have a relatively uniform particle size (approximately 90 nm). Low-intensity diffraction peaks are present in the BC material, resulting from coconut shell growth and the accumulation of CaCO3. Figure 2a The diffraction peaks of BC-MnOx-500 also shifted to higher angles and some new low-intensity diffraction peaks appeared. The diffraction peaks at 18.0, 28.9° and 35.1, 40.5° correspond to Mn3O4 and MnO substances, respectively, where θ is the angle. Figure 2b The FTIR results for BC and BC-MnOx-500 are shown. BC mainly contains molecules located at 3435, 1621, 1272, and 984 cm⁻¹. -1 The functional groups corresponding to -OH, C=C, C=O and CH are present at 500 and 630 cm⁻¹. -1 Two new absorption peaks appeared at the point, which correspond to the stretching vibration of the Mn-O bond, indicating that manganese oxides are loaded on the surface of biochar.

[0069] Example 2:

[0070] This embodiment provides a method and mechanism for removing copper humate complexes of different molecular weights from manganese oxide-modified biochar, including the following steps:

[0071] (1) Removal conditions analysis: A certain amount of BC-MnOx-500 (0.5, 1.0, 1.5 and 2.0 g / L) and H2O2 (100, 150, 200, 250 and 300 mM) were added to 20 mL of HA-Cu complex solution, and then placed in a constant temperature shaker at 150 rpm and set temperature for continuous removal for 10 h. Figure 3a and Figure 3b The removal efficiency of biochar modified with different amounts of manganese oxide for Cu and TOC was investigated. Firstly, by comparing the results of different amounts of the same component, it was found that the Cu removal rate of UF5-Cu was basically independent of the amount of material used, and the removal rate was generally above 90%. Figure 3a However, the TOC removal rate is directly proportional to the amount of material used. Figure 3b The removal rates of other components, Cu and TOC, increased with the increase of modified biochar material dosage, indicating that increasing the amount of modified biochar can better achieve the removal of Cu and humic acid. Secondly, comparing the removal performance of different components at the same material dosage revealed that the single Fenton reaction (hydroxyl radical oxidation technology) partially removes HA-Cu by destroying the HA-Cu complex structure through the autocatalytic reaction of Cu; however, the removal rate of Cu decreases with increasing humic acid molecular weight, as high molecular weight HA has a more complex structure, thus increasing the difficulty of Cu removal, while the TOC removal rate is not significantly correlated with molecular weight. Based on the TOC removal performance, it was found that when the dosage reaches 1.5 g / L, more than 90% of the TOC in the five components can be removed. BC-MnOx-500 material can effectively remove HA-Cu of different molecular weights, but because high molecular weight HA-Cu contains more difficult-to-degrade aromatic substances, its removal is more difficult than that of low molecular weight HA-Cu. Figure 4a and Figure 4b A comparison of Cu and TOC removal rates under different H2O2 dosage conditions. First, from... Figure 4a The results show that the removal rate of Cu in the UF5-Cu component is basically independent of the amount of H2O2 added (>90%), indicating that UF5-Cu is easily adsorbed and removed; however, the TOC removal rate of UF5-Cu is basically directly proportional to the amount of H2O2 used. Furthermore, the removal rates of Cu and TOC in other components are also basically directly proportional to the amount of H2O2 used. Figure 5a A large number of hydroxyl radicals (HO·) were detected in the removal system, indicating that H2O2 plays an important role in the removal of HA-Cu. Secondly, with the same H2O2 dosage, the Cu removal rate gradually decreases with increasing molecular weight, making the removal of high molecular weight HA-Cu more difficult. This can be achieved through… Figure 5b UV-Vis analysis revealed that the absorbance of the solution system after removal increased with increasing complex molecular weight, demonstrating that high molecular weight copper humate complexes are more difficult to remove than low molecular weight complexes. Ultimately, the optimal dosages of BC-MnOx-500 and H2O2 were determined to be 1.5 g / L and 500 μL (250 mM), respectively.

[0072] (2) Investigation of influencing factors: The modified biochar dosage was 1.5 g / L, H2O2 was 250 mM, and the pH of the copper humate solution was adjusted with 0.1 M nitric acid and sodium hydroxide solution (to 4, 6, 7, 8 and 10, respectively); secondly, the coexisting cations and anions in the water body (10 mM Ca) were analyzed. 2+ Na + CO3 2- and SO4 2- Inductively coupled plasma mass spectrometry (ICP-MS) was used to analyze the concentrations of Cu and Mn during the removal process. Regarding the effect of pH on the removal performance of copper humate complexes, there was no significant change in the removal rates of Cu and TOC. Figure 6a and 6b Under the same pH conditions, the removal rate of Cu from different components decreased to varying degrees with increasing molecular weight, while the removal rate of TOC showed no significant correlation with molecular weight. Acidic conditions favored the Fenton reaction but also affected the stability of BC-MnOx-500. At pH=4, the Mn dissolution concentration reached 3.5 mg / L, and the Mn concentration decreased with increasing pH (remaining below 2 mg / L). Considering both removal performance and material stability results, it is clear that pH has no obvious effect on HA-Cu removal, but it does have a certain impact on the stability of BC-MnOx-500 material. This indicates that determining relatively suitable solution conditions is necessary for the removal of HA-Cu using BC-MnOx-500. Figure 7a and Figure 7b To illustrate the effect of coexisting ions on Cu and TOC removal, Na + The removal of Cu from UF5-Cu and UF4-Cu components had little effect, but its inhibition ability increased with increasing molecular weight; conversely, Ca... 2+ The presence of [a substance] promotes Cu removal; even in the UF1-Cu fraction, the removal rates of Cu and TOC can still reach around 90%, possibly due to [the presence of Ca]. 2+ The presence of [certain substances] affects the complexation of Cu and HA, leading to the easy adsorption or formation of gel precipitates of HA-Cu complexes, or [the presence of Ca]. 2+ This may favor the Fenton reaction, thereby promoting the production of HO·, therefore Ca 2+ The addition of [a substance] is beneficial for the removal of HA-Cu. When anions coexist, SO42- 2- The removal of Cu from the UF2 / UF1-Cu fraction was slightly inhibited, but there was no significant effect on TOC. This may be because SO42- 2- It reacts with HO·, consuming free radicals and also producing SO4, which can be used to degrade HA. - When CO3 coexists 2- The removal of Cu from any component was significantly inhibited by CO3, which can be attributed to CO3. 2-It acts as a quencher for HO·, reducing the concentration of free radicals and thus decreasing removal capacity. Furthermore, due to CO3... 2- The presence of the substance affected the determination of inorganic carbon, so the TOC removal rate under these conditions could not be analyzed. Ambient temperature is one of the factors affecting HA-Cu removal, and studies have shown that high-temperature conditions are favorable for the Fenton reaction. Figure 8a and 8b The removal performance of HA-Cu at 25, 30, and 35 °C was demonstrated. Temperature had little effect on the removal of Cu from the low molecular weight components UF5 / UF4 / UF3-Cu, but the removal rate of UF2 / UF1-Cu increased significantly with increasing temperature. At 35 °C, the removal rates of Cu and TOC reached over 85% and 95%, respectively, indicating that higher removal temperatures are beneficial for the removal of HA-Cu. High temperature conditions are conducive to the generation of more free radicals in the Fenton reaction, thereby better destroying the complex structure of HA-Cu.

[0073] (3) Removal mechanism analysis: The EEM spectra of the five HA-Cu components changed significantly at different removal times. At 0 h, the UF5 / UF4 / UF3-Cu components exhibited weak fluorescence peaks ( Figure 9 a0, b0, and c0) and the UF2 / UF1-Cu component showed no fluorescence peaks. Figure 9 d0 and e0), but after 1 hour of removal, all five HA-Cu components showed strong fluorescence peaks (d0 and e0). Figure 9 While the fluorescence peaks of the five HA-Cu components (a1-e1) gradually decreased with increasing removal time, they essentially disappeared after 8 hours. This indicates that HO· generated in the system can destroy the complex structure of HA-Cu or degrade HA, generating small-molecule organic products with strong fluorescence peaks. However, HO· continues to destroy these intermediate products, causing them to decompose into other small-molecule organic compounds without fluorescent functional groups or complexes with copper. Simultaneously, various intermediate products are adsorbed by BC-MnOx-500, resulting in a phenomenon where the fluorescence intensity first increases and then decreases with time. Furthermore, comparing the EEM spectra of HA-Cu with different molecular weights at the same removal time revealed that the fluorescence intensity gradually increased with increasing humic acid molecular weight. Especially after 4 hours of removal, the high-molecular-weight components (UF2 / UF1-Cu) still exhibited strong fluorescence peaks, proving that high-molecular-weight HA-Cu is more difficult to remove. In summary, the EEM spectra results indicate that HA-Cu with different molecular weights can be effectively removed under the catalysis and adsorption of BC-MnOx-500 material, but the removal pathways and rates are significantly different, and the removal is closely related to molecular weight. CE analysis was performed on the changes in the HA-Cu structure before and after complexation and during the removal process of the five HA-Cu components. Figure 10Comparing the CE spectra of the same component at different removal times, the absorption peaks shifted towards decreasing time and gradually weakened with increasing removal time, disappearing completely at 10 h. This indicates that in the Fenton system catalyzed by BC-MnOx-500, the HA-Cu complex structure gradually disintegrated, generating other low-molecular-weight organic matter or copper complexes, such as copper complexes of short-chain hydrocarbons. Meanwhile... Figure 11 It is evident that flocculent material remains on the surface of the material after removal, which may be intermediate and final products adsorbed onto the material surface. The FTIR spectrum in Figure 12a shows that at 2900 and 1870 cm⁻¹... -1 The presence of characteristic CH and C=O absorption peaks not found in BC-MnOx-500 indicates that organic matter has been adsorbed onto the material surface. Combined with the XPS results in Figures 12b and 12c, it can be seen that nitrogen-containing substances and CuO are both present on the material surface. Therefore, the humic acid-complexed copper complex undergoes complex structure breakdown and adsorption removal under the action of BC-MnOx-500. The catalytic and adsorption effects of BC-MnOx-500 achieve the simultaneous removal of HA and Cu.

[0074] Contents not described in detail in this specification are prior art known to those skilled in the art. It is hereby indicated that the above description is intended to help those skilled in the art understand this invention, but does not limit the scope of protection of this invention. Any equivalent substitutions, modifications, improvements, and / or simplifications of the above descriptions that do not depart from the essential content of this invention fall within the scope of protection of this invention.

Claims

1. A method for removing copper humates of different molecular weights by adsorption and synergistic oxidation using manganese oxide-modified biochar, characterized in that... The method involves dividing HA-Cu according to molecular weight, removing HA-Cu with a molecular weight below 1 kDa by adsorption using manganese oxide-modified biochar, and removing HA-Cu with a molecular weight above 1 kDa by a combination of adsorption and catalytic oxidation using manganese oxide-modified biochar. The catalytic oxidation utilizes hydroxyl radicals to degrade long-chain alkanes, benzene rings, and / or heterocyclic copper humic acid complexes in high molecular weight humic acid HA into small molecule organic matter and / or small molecule complexes of Cu that can be adsorbed. The manganese oxide-modified biochar is prepared using the following steps: Step 1: Mix biochar BC and anhydrous ethanol to form a first mixture; Step 2: After continuously stirring the first mixture for 4 hours, slowly add KMnO4 solution to form the second mixture; Step 3: After stirring the second mixture for 2 hours, filter it with 0.45 μm qualitative filter paper to obtain the retentate. Wash the retentate with ultrapure water to obtain the initial sample. Step 4: Place the initial sample in a constant temperature drying oven at 90℃ for 12 hours to obtain the intermediate sample; Step 5: Place the intermediate sample in a tube furnace and heat it to 500℃ at a rate of 5℃ / min under nitrogen atmosphere protection. Hold the temperature for 1 hour. After the program is completed, automatically cool it to room temperature to obtain the final sample, i.e., manganese oxide modified biochar. Name the final sample BC-MnOx-500, where x is a positive integer. In step 1, BC is 60-80 mesh coconut shell biochar granules. 1g of BC and 20mL of anhydrous ethanol are selected. In step 2, 20mL of KMnO4 solution is used. The concentration of KMnO4 solution is 0.1M. The following steps were taken to analyze the performance of manganese oxide-modified biochar in removing copper humates of different molecular weights: Step A: Prepare copper humate complex solution; Step B, performance analysis: BC-MnOx-500 and H2O2 were added to the copper humate complex solution to form a mixture. The mixture was placed in a constant temperature shaker at 150 rpm and set temperature and rotated continuously for 10 hours. Samples were taken every 1 hour. The samples were filtered through a 0.45 μm polyethersulfone (PES) membrane, acidified with 2 wt% HNO3, and the concentrations of Cu and Mn were analyzed by inductively coupled plasma mass spectrometry. The total organic carbon (TOC) content of the un-acidified filtered samples was analyzed using an organic carbon analyzer. Step C, Analysis of influencing factors: Under the determined dosage conditions, the effects of pH value, common coexisting ions and different temperatures on the removal performance of HA-Cu complex and the stability of the material were analyzed. Step D, Analysis and Testing: Three-dimensional fluorescence and capillary electrophoresis were used to analyze the structural changes of HA-Cu with different molecular weights during the removal process. The changes in material morphology and structure were combined to support the removal mechanism of copper humate complex.

2. The method for removing copper humates of different molecular weights by adsorption and synergistic oxidation using manganese oxide-modified biochar according to claim 1, characterized in that, Step A includes: dissolving 1g of humic acid solid powder in 1L of NaOH solution (0.025M concentration), stirring at room temperature in the dark for 3 hours, filtering using a 0.45μm aqueous filter membrane, and adjusting the pH of the obtained humic acid (HA) stock solution to 7 with 0.1M HNO3. Ultrafiltration fractionation is then used to obtain HA solutions with different molecular weights, labeled UF1 to UF5. UF1 corresponds to a molecular weight >100kDa, 100kDa ≥ UF2 corresponds to a molecular weight >30kDa, 30kDa ≥ UF3 corresponds to a molecular weight >10kDa, 10kDa ≥ UF4 corresponds to a molecular weight >1kDa, and UF5 corresponds to a molecular weight <1kDa. Cu is added to each of the five different molecular weight HA solutions. 2+ Five mixed solutions were then placed in a constant temperature shaker at 25°C and equilibrated for 12 hours to achieve complete complexation. The complexed solutions were named UF1-Cu, UF2-Cu, UF3-Cu, UF4-Cu and UF5-Cu, respectively.

3. The method for removing copper humates of different molecular weights by adsorption and synergistic oxidation using manganese oxide-modified biochar according to claim 1, characterized in that, The amounts of BC-MnOx-500 added in step B, expressed in g / L, were 0, 0.5, 1.0, 1.5, and 2.0, respectively, and the amounts of H2O2 added, expressed in mM, were 100, 150, 200, 250, and 300, respectively.

4. The method for removing copper humates of different molecular weights by adsorption and synergistic oxidation using manganese oxide-modified biochar according to claim 1, characterized in that, In step C, the pH conditions are set to 4, 6, 7, 8, and 10, respectively. Common coexisting ions include Ca2+. 2+ Na + CO3 2- and SO4 2- The different temperature conditions were set to 20℃, 25℃ and 30℃ respectively.

5. The method for removing copper humates of different molecular weights by adsorption and synergistic oxidation using manganese oxide-modified biochar according to claim 1, characterized in that, In step D, capillary electrophoresis and three-dimensional fluorescence detection are used to determine the intermediate products of the removal process based on the different peak positions. Scanning electron microscopy, Fourier transform infrared spectroscopy, and X-ray diffraction are used to analyze the morphology and structure of the removed material to help determine the removal mechanism.

Citation Information

Patent Citations

  • Modified bio-char as well as preparation method and application thereof

    CN106390940A

  • Nano-manganese-oxide-modified biomass charcoal, preparation method and method for removing copper citrate

    CN110743495A